Development of Vocabulary Cards as Learning Media to Improve the English Vocabulary of Fourth Grade Elementary School Students - Andriani, Cesilia; Novrianti, Novrianti; Pertiwi, rahmi; Masnur, Alkadri (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2025)
The purpose of this research was to develop vocabulary card learning media to improve the English vocabulary mastery of fourth-grade elementary school students. This study was motivated by the limited availability of engaging visual learning media in elementary schools, accompanied by students’ low English vocabulary mastery. This development aimed to describe and present an overview of vocabulary card learning media as an alternative instructional tool, as well as to determine the validity and practicality levels of the developed product.This research employed a Research and Development (R&D) approach using the 4D development model, which consists of the Define, Design, Develop, and Disseminate stages. The development stage served as the benchmark for the success of the media, as it involved expert assessments through validity tests and product trials for practicality testing. The validity tests consisted of two phases: the media and linguistic validity tests conducted by media and language experts, and the content validity test conducted by the fourth-grade homeroom teacher of SD IT Baitul Hamdi. After the validity tests, a practicality test was conducted with the fourth-grade students of SD IT Baitul Hamdi.The vocabulary card learning media, covering the topics It’s Seven O’Clock, Daily Activities, and This Is My Bicycle, obtained a “very valid” rating in the first media and linguistic validity test with an average score of 4.57 from two validators and was declared feasible with revisions. In the second validity test, the media achieved an overall “very valid” score of 4.97 and was deemed suitable for field testing without revisions. The content validity test achieved a “very valid” result with an average score of 4.89, while the practicality test yielded a “very practical” result with an overall average of 4.55. Based on the validity and practicality results, it can be concluded that the vocabulary card learning media is ready to be implemented and is practical for use in the teaching and learning process. The disseminate stage was carried out by distributing the product to the Teacher Working Group (KKG) of Cluster 6, which consists of representatives from nine elementary schools in the research area through a representative teacher from SD IT Baitul Hamdi, with the handover proven by an official handover letter.